2022
DOI: 10.1109/access.2022.3211941
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Electricity Load Forecasting Based on Temporal Fusion Transformer Model

Abstract: Electricity load forecasting plays an important role in the operation of power systems. Inaccurate forecast would reduce the safety of power supply and affect the economic and social activities as well as national defense and security. In addition, the forecast results also support decision-making on electricity generation and market transactions. Traditional methods such as AR, ARIMA, SARIMA have been widely used to forecast short term electricity load. Recently, load forecasting based on artificial and deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Transformer was proposed and widely used in computer vision and natural language processing. Numerous studies have shown that it has the potential to improve predictions [29,45]. Informer is an efficient transformer-based model [30] designed for LSTF, and its ProbSparse self-attention effectively reduces time complexity.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Transformer was proposed and widely used in computer vision and natural language processing. Numerous studies have shown that it has the potential to improve predictions [29,45]. Informer is an efficient transformer-based model [30] designed for LSTF, and its ProbSparse self-attention effectively reduces time complexity.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…In addition, Pelekis et al [44] compared the accuracy of TCN and N-BEATS in STLF settings for the case of the Portuguese national load at a 15-minute resolution, with N-BEATS resulting to superior forecasts. With respect to transformers, Zhang et al [66] evaluated a time augmented transformer for STLF on the electrical load data of New South Wales in Australia, Lim et al [33] validated temporal fusion transformers for STLF on the UCI Electricity Load Diagrams Dataset [60], while Huy et al [25] employed the latter architecture to forecast the load of Hanoi city using weather and calendar features.…”
Section: Related Workmentioning
confidence: 99%
“…The LSTM-based method proposed by Memarzadeh and Keynia [49] has been validated successfully on load and price data collected from the Pennsylvania-New Jersey-Maryland (PJM) and Spain electricity markets. Similarly, advanced NN architectures have gained popularity [4,13,50], introducing innovative deep STLF approaches based on feed-forward [51,52], convolutional [53], or transformer [54,55] setups.…”
Section: Related Workmentioning
confidence: 99%